Excess prenatal folic acid supplementation alters cortical DNA methylation and gene expression networks - Haghani, Viktoria; Ali, Sara Mohsen; Cannizzaro, Noemi; Green, Ralph; LaSalle, Janine M.; Zarbalis, Konstantinos S. (Frontiers in Nutrition, 2025)
IntroductionFolate is crucial for various biological processes, and deficiencies during pregnancy are linked to increased risk for neural tube defects and neurodevelopmental disorders. As a proactive measure, folic acid fortification of staple foods has been mandated in many countries, in addition to dietary supplementation recommendations during pregnancy. However, the risks of excess prenatal folic acid supply have yet to be fully understood.MethodsTo better appreciate molecular changes in mouse brain exposed to in utero 5-fold folic acid excess over normal intake, we investigated the transcriptome and methylome for alterations in gene networks.ResultsRNA-seq analysis of cerebral cortex collected at birth, revealed significant expression differences in 646 genes with major roles in protein translation. Whole genome bisulfite sequencing revealed significant differences in 910 differentially methylated regions including functions enriched in glutamatergic synapse, neurodevelopmental, and glutathione pathways.DiscussionThese molecular alterations conceivably present risks to brain development and provide functional congruencies with disruptions in neuronal connectivity maps that we have described in previous work, underscoring the potential for excess prenatal folic acid exposure to disrupt developing metabolic and neurological pathways.